Pengaruh Hym-248 Terhadap Metamorfosis Planula Karang Acropora spp Di Pulau Sambangan, Kepulauan Karimunjawa - Afriandi, Andi; Trianto, Agus; Wijayanti, Diah Permata (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Multispecies synchronous spawning of scleractinian corals was first documented on Great Barrier Reef, Australia in the early 1980s. Settlement as the next stage of planulae’s life plays an important role in the persistence of coral colony. HYM-248 is one type of peptide synthesis, which has been shown to make Acropora spp planulae metamorphosed. This study aims to determine the influence of Hym-248 on Acropora spp planulae’s metamorphosed. The method is a eksperimental laboratoris, Slick is collected from Sambangan Island, Karimunjawa Archipelago when spawning occurs simultaneously in March. Provision of Hym-248 administered in 5 different doses, namely: 5x10-7; 1x10-6; 2x10-6; 5x10-6; 1x10-5 M and one control treatment without peptide. The results showed, Hym-248 was able to accele metamorphosis and attachment of planulae from the slick. Planulae started metamorphosis after 8 hours of treatment 1x10-6 M concentration. All of which planulae are in Iwaki wells that contained of Hym-248 are metamorphosed and even to stick. On control treatment only changes shape into an oval until the end of the observation time.